Pengaruh Terapi Tawa terhadap Kualitas Tidur pada Lansia di Unit Pelayanan Teknis Panti Sosial Lanjut Usia (UPT PSLU) Kabupaten Jember (The Effect of Laughter Therapy on Sleep Quality of Elderly in Long-Term Care Jember) - Ananta Erfrandau; Murtaqib Murtaqib; Nur Widayati (Pustaka Kesehatan, 2017)
Age is a factor that can influence sleep quality. Sleep quality decreases with aging and the complaintsof sleep become common among elderly. This study aimed to analyze the effect of laughter therapy onsleep quality of elderly in Long-Term Care Jember. The design of study was randomized control grouppretest-posttest design. The sample was 30 respondents, 15 respondents is intervention group and 15respondents is control group. Sleep quality was measured by using Pittsburgh Sleep Quality Index(PSQI). The data were analyzed by t test, Wilcoxon test, and Mann-Whitney test with significance levelof 0.05. The result revealed a significant difference of sleep quality before and after laughter therapy inthe treatment group (p: 0.001), and there was no significant difference between pretest and posttest inthe control group (p: 0.082). Mann-Whitney test showed a significant difference of sleep qualitybetween the treatment group and the control group after laughter therapy (p: 0.000). The percentageof elderly sleep quality before laughter therapy in the treatment group that is bad 100%, while afterlaughter therapy that is either equal to 100% which means there is an increase in the quality of sleepof 100%. Percentage of quality sleep before therapy in the control group of poor by 100%, while after abad sleep therapy quality percentage is 100%, which means no increase in the quality of sleep in thecontrol group It can be concluded that there was a significant effect of laughter therapy on sleepquality of elderly in Long-Term Care Jember. Laughter therapy can be applied to improve sleep qualityin elderly people.Keywords: sleep quality, elderly, laughter therapy